THE EFFECT OF WORK-FAMILY CONFLICT AND WORKLOAD ON EMPLOYEE PERFORMANCE MEDIATED BY WORK STRESS ON FEMALE EMPLOYEES WITH FAMILIES IN THE FISCAL POLICY AGENCY - Masye Tualai, Marhaeny; M. Havidz Aima (Dinasti International Journal of Management Science, 2022)
This study aims to analyze the effect of work-family conflict and workload on employee performance mediated by work stress on female employees with families at the Fiscal Policy Agency. The population of this study is 70 people. This research is quantitative research with the analytical method using Structural Equation Model-Partial Least Square (SEM-PLS). The results showed that work-family conflict had a significant effect on work stress; work-family conflict had a significant effect on employee performance; workload had a significant effect on work stress; workload had a significant effect on employee performance; work stress had a significant effect on employee performance; work-family conflict and workload simultaneously have a significant effect on employee performance; work-family conflict, workload and work stress simultaneously have a significant effect on employee performance; work stress significantly mediates work-family conflict on employee performance and work stress significantly mediates the effect of workload on employee performance